The establishment-size wage premium: evidence from European countries - Thierry Lallemand; Robert Plasman; François Rycx (Institute for the Study of Labor (IZA), 2005)
This study examines the magnitude and determinants of the establishment-size wage premium in five European countries using a unique harmonised matched employer-employee data set. Findings show the existence of a significant positive wage premium in all countries, even when controlling for labour quality, working conditions, monitoring, sectoral and regional effects, bargaining institutions, job stability, and concentration of skilled workers. In cross-national perspective, results support the existence of an inverse relationship between the size wage gap and the degree of corporatism. Final results indicate that the size wage premium is generally larger in the manufacturing sector and for blue-collar workers.
Keywords: J31; 330; establishment-size and wages; matched employee data; Europe; Betriebsgröße; Lohnstruktur; Belgien; Dänemark; Irland; Italien; Spanien